Coal and biomass co-pyrolysis in a fluidized-bed reactor: Numerical assessment of fuel type and blending conditions. (1st September 2020) - Ismail, Tamer M.; Banks, S.W.; Yang, Y.; Yang, Haiping; Chen, Yingquan; Bridgwater, A.V.; Ramzy, Khaled; Abd El-Salam, M.
Highlights: Investigation on the co-pyrolysis characteristics of biomass and coals were discussed. Numerical model provides a promising way to simulate the copyrolysis on FB. Obvious synergy effect is generally achieved under higher biomass to coal ratios. Biomass co-pyrolysed with coal of 70% is accepted, without real adjustment of FB. Abstract: Co-pyrolysis is one of the most promising options for using coal and biomass because coal is low in hydrogen and biomass can supplement the hydrogen content to make a more valuable and reactive product gas. The mixture of coal and biomass is prepared, with the mass ratio of biomass varying between 0 and 100%. Due to limitations in experimental methods, the data points measured in these studies are coarse and therefore, insufficient for kinetic energy analysis and model comparison. Therefore, a mathematical model has been proposed to combine a study of the influence of experimental parameters with different materials to understand better the effect of these parameters on pyrolysis with the rigorous control of experimental conditions in terms of precision and repeatability. The advantages of mathematical modelling co-pyrolysis make it possible to design a reaction scheme capable of describing this phenomenon and extracting kinetic parameters, making it possible to compare fuels, which can be used for the simulation of this process in thermal power plants. The experimental analysis of measured co-pyrolysis data was taken from literature work to validate the proposed model. The numerical model results are in good agreement with the experimental data for co-pyrolysis. The most significant degree of synergetic effects on the product yields was observed at 600 °C and a biomass blending ratio of 70 wt%. Furthermore, the improvement of char reactivity also identifies the synergies in co-pyrolysis.